Retail Store Brand Commitment Study of Big Bazaar and Pantaloons - Shivaji Mohinta; Uma Shankar Singh; Uma Sankar Mishra (International Journal of Supply Chain Management, 2017)
The study is all about the brand commitment by retail stores in the eyes of customers. The extensive literature review done finds the problem that in this competitive environment where the consumer choices fluctuate due to various reasons, it is getting very challenging for stores to maintain the customers commitment towards brand at the one end. At the other end to sustain in this war business houses need to hold their customer base, making the customers more loyal. The objectives defined to find the solution for this research problem are to know the level brand commitment of the brands taken in study, to get the comparison of brands commitment and to find the opportunity to expand the brands business. A structured questionnaire administered among 550 respondents. The data analyzed using SPSS with t- test and paired t- test. The outcome of paired t- test for the 6 pairs shows that there is no significant difference in opinion of respondents for the variables of brand commitment for both the brands big bazaar and pantaloons.